Factors influencing Youth Entrepreneurial Intention: A Study on Fourth-Year Students of the Faculty of Management Studies and Commerce, University of Jaffna - Tharshiga, P.; Vithurshika, R.; Subramaniam, V.A.S (Faculty of Business Studies, University of Vavuniya, Sri Lanka, 2025)
Youth entrepreneurial intention is influenced by various factors that shape the willingness and motivation of individuals to engage in entrepreneurial activities. The study aims to analyse factors influencing youth entrepreneurial intention. To achieve the research objective, the study focuses on fourth-year students pursuing only management studies. A stratified random sampling method was used to collect two hundred data. Based on the Multiple regression analysis, the study concludes that capital is the most critical factor influencing entrepreneurial intentions, emphasising the vital role of financial resources in achieving business success. It also highlights the significance of educational programs, as academic exposure tends to foster greater entrepreneurial ambition. Additionally, familial support is shown to enhance motivation for entrepreneurship. In contrast, support and motivation from friends proved to have an insignificant effect, suggesting that peer influence may not be as pivotal. The study recommends that financial institutions should make funding more accessible and that educational institutions should improve entrepreneurial training. It also encourages families to support their members' business endeavours actively. Moreover, implementing structured mentorship and networking opportunities could help address the limited impact of peer influence. Future research should delve into industry-specific entrepreneurship, cultural influences, and psychological factors such as risk-taking and resilience. Longitudinal studies are particularly encouraged to evaluate how these factors contribute to long-term business sustainability. These insights will be valuable for policymakers, educators, and researchers in crafting effective strategies to promote entrepreneurship and drive economic growth. Additionally, highlighting successful entrepreneurial stories within the community could inspire students and alleviate their apprehensions about starting a business.
Keywords: Capital; Friends’ support; Motivation; Education programme; Family support; Youth entrepreneurial intention